European forest sinks and climate targets: past trends, main drivers, and future forecasts - Hyyrynen, Matti; Ollikainen, Markku; Seppälä, Jyri (Springer Nature, 2023)
We examine the evolution of European net sinks towards 2030 and the European Union’s (EU) climate neutrality target by 2050. The EU’s current land use policy for 2021–2030 is divided into two periods: 2021–2025 and 2026–2030. The national inventory data from several databases and statistical analyses are used to examine the trends and drivers and to forecast future forest sinks and the net sinks of the land use, land use change and forestry (LULUCF) sector. Our forecasts suggest that national forest sinks will be short of the agreed forest reference levels in most member states in 2021–2025, with a total of 128 MtCO2eq. For 2026–2030, the net sink for the whole EU LULUCF sector will be short of the EU target by 298 MtCO2eq. Thus, most member states must design more efficient LULUCF policies to fulfil their national targets. Furthermore, the decreasing trends in the LULUCF sinks also emphasize the need to reduce emissions and to increase the sinks in most member states so that the EU can achieve its climate neutrality goal by 2050.
Keywords: Climate change mitigation; EU LULUCF regulation; Forest sinks; Panel data analysis; Time series analysis